Design Construction of an Automatic Liquid Soap Dispenser Based on an Infrared (IR) Sensor - Riski Riski; Kemas Muhammad Wahyu Hidayat; Zulhipni Reno Saputra Elsi (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
This study aims to design and implement an automatic liquid soap dispenser based on an infrared (IR) sensor to Hand hygiene is an important factor in preventing the spread of disease, especially those caused by bacteria and viruses. The use of conventional liquid soap dispensers still requires physical contact, thus potentially causing cross-contamination. Therefore, this study aims to design and build an automatic liquid soap dispenser based on infrared (IR) sensors that can work without contact. The research method used is Research and Development (R&D), which includes the stages of needs analysis, system design, prototyping, and tool testing. This tool uses an infrared sensor to detect the presence of hands, Arduino Uno as the main controller, and a TDR Delay module to set the active duration of the liquid soap pump. When a hand is detected by the infrared sensor, the signal will be processed by the Arduino Uno to activate the delay module, then the DC pump will turn on for a predetermined duration so that liquid soap is dispensed automatically. After the set time is reached, the pump will automatically turn off and the system will return to standby mode. The test results show that the automatic liquid soap dispenser can work well and responsively in detecting hands and dispensing liquid soap consistently according to the set duration. This system is able to reduce direct physical contact, improve hygiene, and has a simple design, is energy efficient, and is easy to implement.